2019
DOI: 10.1109/jphot.2018.2885091
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Three-Hump Phosphor-Coated White Light-Emitting Diodes for Healthy Lighting by Genetic Algorithm

Abstract: In this paper, we carry out the theoretical spectral optimization and perform experiments by varying temperature and electrical current primarily on one-phosphor-coated three-hump white light-emitting diode (LED) for healthy indoor or outdoor lighting by using the genetic algorithm (GA). White light with low circadian action factor (CAF) is propitious for bedroom lighting to help people relax and to promote sleep, whereas high CAF white light is beneficial for increasing working efficiency in the working place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The parameters that are allowed to change are the emission peak wavelengths of blue LED, green perovskite, red LED, and red QD. The fitting parameters of blue and red LEDs are from [110], the SPDs of green perovskite and red QDs are from [99], the SPD of KSF phosphor is from [111], and that of SLA phosphor is from [112]. All of the SPDs are plotted in Figure 10b and the fitting parameters (including ∆λ) used in the SP7 model are listed in Table 1.…”
Section: Lcd Backlight Applicationsmentioning
confidence: 99%
“…The parameters that are allowed to change are the emission peak wavelengths of blue LED, green perovskite, red LED, and red QD. The fitting parameters of blue and red LEDs are from [110], the SPDs of green perovskite and red QDs are from [99], the SPD of KSF phosphor is from [111], and that of SLA phosphor is from [112]. All of the SPDs are plotted in Figure 10b and the fitting parameters (including ∆λ) used in the SP7 model are listed in Table 1.…”
Section: Lcd Backlight Applicationsmentioning
confidence: 99%
“…For a light source, its non-visual biological effect on human beings is attributed to the third type of photoreceptors called as intrinsic photosensitive retinal ganglion cells (ipRGCs), which play key roles in the formation and release of melatonin, cortisol, and other hormones [19]. The circadian action factor (CAF), defined as (9), is frequently used to quantitatively describe the intensity of non-visual biological effects [8]- [13]. The larger value of CAF, the greater non-visual biological effects on human beings.…”
Section: Circadian Action Factor Modeling Of Multi-pc White Led Sourcesmentioning
confidence: 99%
“…It has been found that, lighting with low CAF is suitable at night to help people relax and fall asleep, while lighting with high CAF is recommended in the daytime to increase working efficiency. In [13], the temperature dependency and current dependency of CAF have been qualitatively studied, and both of them present evidently linear. Though without quantitative relations proposed, their observations become meaningful guidance to quantitatively model for CAF versus temperature and current.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] The LED technology, which offers high versatility in controlling the spectral power distribution (SPD) of light sources and dimming, allows for immediately meeting the needs of dynamic circadian lighting. A straightforward approach to such lighting is the development of white LEDs with variable correlated color temperature (CCT), [18][19][20][21][22][23][24][25][26][27][28][29][30] which follows the periodic variation of color temperature of natural light from the Sun and blue sky between 2000 and 20 000 K. The previous studies have focused on the circadian action factors (CAFs) 31 of the tunable white LEDs, 22-24, 26,27,30 in addition to the color temperature, the general color rendering index (R a ), 32 the color fidelity (R f ), 33 color gamut (R g ), 33 luminous efficacy of radiation (LER) and luminous efficacy (LE). And try to make the CAFs of white LEDs less than that of natural light at low CCT, and higher than that of natural light at high CCT.…”
Section: Introductionmentioning
confidence: 99%